Microstructural evolution of carbon fiber reinforced SiC-based matrix composites during laser ablation process. Issue 12 (December 2019) - Dang, Xiaolin; Yin, Xiaowei; Fan, Xiaomeng; Ma, Yuzhao; Wang, Jiangtao; Ju, Panfei; Song, Hongwei
Abstract: In this work, four different carbon fiber reinforced SiC-based matrix composites (C/SiC) were prepared, and microstructure evolution during laser ablation process was characterized. Laser irradiation provided a special high-temperature environment up to 3500 °C. For all four composites, different morphologies can be obtained in the transition region due to the oxidation of different matrices. While only needle-shaped carbon fiber and nanolayered carbon without any matrix remained in the central region, indicating that graphitization process occurred in the center, resulting from the high-temperature and low-oxygen environment in the laser process. Therefore, the laser ablation of C/SiC composites is controlled by chemical and physical erosion, and mainly by the physical erosion in the center.